2015
DOI: 10.1007/s10552-015-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Childhood lymphoma incidence patterns by ICCC-3 subtype in Mexico City metropolitan area population insured by Instituto Mexicano del Seguro Social, 1996–2010

Abstract: There was a trend toward a reduced incidence, for some lymphoma subtypes, in particular for NOS lymphomas, which may be the result of improvement in diagnostic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At the present time, no clear conclusion can be drawn for lymphomas (Table S2): a positive significant trend was observed in nine studies, [18][19][20][21][22][23][24][25][26] with different results by subgroup of lymphoma, and with a leveling off in the most recent years for three of those studies 20,22,26 ; four studies generated nonsignificant results [27][28][29][30] (for White non-Hispanics in Gittleman et al 28 ); and only one study, conducted in Mexico, evidenced a significant decreasing trend, over 1996-2010. 31 The results for germ cell tumors over recent periods were also quite heterogeneous (Table S10) 19 but not in the USA, 21 Germany, 32,33 Great Britain 20 or Canada. 29 Results for the USA are not clear-cut but no increase was found overall.…”
Section: Temporal Variations Of Childhood Cancersmentioning
confidence: 99%
“…At the present time, no clear conclusion can be drawn for lymphomas (Table S2): a positive significant trend was observed in nine studies, [18][19][20][21][22][23][24][25][26] with different results by subgroup of lymphoma, and with a leveling off in the most recent years for three of those studies 20,22,26 ; four studies generated nonsignificant results [27][28][29][30] (for White non-Hispanics in Gittleman et al 28 ); and only one study, conducted in Mexico, evidenced a significant decreasing trend, over 1996-2010. 31 The results for germ cell tumors over recent periods were also quite heterogeneous (Table S10) 19 but not in the USA, 21 Germany, 32,33 Great Britain 20 or Canada. 29 Results for the USA are not clear-cut but no increase was found overall.…”
Section: Temporal Variations Of Childhood Cancersmentioning
confidence: 99%
“…19 Data from our study showed a decreasing trend, and in a more detailed study of lymphomas that was performed by our group, the mixed cellularity subtype decreased in Hodgkin's lymphomas; non-Hodgkin's lymphomas also displayed a decreasing trend, particularly in the unspecified types, which was identified as an improvement in the histopathological diagnosis in recent years. 20 In relation to mortality exclusively, which, as mentioned, is related to the overall efficacy of treatment that is being administered to the population, 6,21 only the data from the period of 2003-2013 should be considered because during this period, the incidence was stable and it could be verified that the incidence differed from what occurred in developed countries, where the cancer mortality in children decreased. 4,7,13,22 This did not occur for the children in our study and in general for Mexican children because similar results were found when cancer mortality for children throughout the country was studied.…”
Section: Artículo Originalmentioning
confidence: 99%
“…In a recent study, we described advanced stages at diagnosis, younger age and low cure rate for NHL in our reference center, even after the addition of rituximab [30]. Recently, detailed data on NHL in Mexican children have been reported from the Instituto Mexicano del Seguro Social (IMSS) [31].…”
Section: Non-hodgkin's Lymphomamentioning
confidence: 99%